2013
DOI: 10.1007/s00701-013-1963-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-transplantation of bone marrow-derived mesenchymal stem cells and nanospheres containing FGF-2 improve cell survival and neurological function in the injured rat spinal cord

Abstract: These results suggest a proliferative, protective, and neural inductive potential of FGF-2 for transplanted hBMSCs, as well as a possible role for sustained FGF-2 delivery along with hBMSCs transplantation in the injured spinal cord. Future studies will be required to ascertain the safety FGF-2-containing HCPNs before clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Thus, 2 critical issues should be addressed to improve the effectiveness of NSC transplantation for SCI repair. First, a passage location for axon growth should be provided (Amr et al, 2014;Binan et al, 2014;Pera et al, 2014); second, a stable microenvironment rich in nutrients and nerve growth factors should be ensured (Paczkowska at al., 2013;Uesaka et al, 2013;Ladewig et al, 2014;Shin et al, 2014). MBL is a new scaffold material and is a natural biomaterial made by removing muscle cells, panniculus adiposus, membrane-associated antigens, and soluble protein; MBL is similar to the neural membrane tube.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 2 critical issues should be addressed to improve the effectiveness of NSC transplantation for SCI repair. First, a passage location for axon growth should be provided (Amr et al, 2014;Binan et al, 2014;Pera et al, 2014); second, a stable microenvironment rich in nutrients and nerve growth factors should be ensured (Paczkowska at al., 2013;Uesaka et al, 2013;Ladewig et al, 2014;Shin et al, 2014). MBL is a new scaffold material and is a natural biomaterial made by removing muscle cells, panniculus adiposus, membrane-associated antigens, and soluble protein; MBL is similar to the neural membrane tube.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviorally, there have been mixed results, with locomotor improvement reported in several studies after contusion injuries (Grulova et al, 2015;Hwang et al, 2011;Kim et al, 2006;Meng et al, 2008;Rabchevsky et al, 1999;Shin et al, 2014;Tsai et al, 2008), and with some (Chen et al, 2015;Goldshmit et al, 2014;Guzen et al, 2012;Kasai et al, 2014;Lee et al, 2008;Tsai et al, 2006) or no (Meijs et al, 2004) functional improvement after complete transection. A human trial using FGF1 and fibrin glue in nine patients with cervical SCI reported improvement in ASIA grade for some patients, as well as some improvement in bowel/ bladder function and reduced neuropathic pain for one patient .…”
Section: Fibroblastic Growth Factorsmentioning
confidence: 93%
“…Intrathecal administration typically involves osmotic pumps to continuously deliver FGF to (or near) the lesion over days or weeks Kojima & Tator, 2002;Lee et al, 1999;Rabchevsky et al, 1999). FGF has also been delivered in association with Schwann cells or peripheral nerve (PN) grafts, released by carriers such as gelfoam, gelatin, fibrin glue, HEMA-MOETACL hydrogels alginate scaffolds or from nanoparticles (Chen et al, 2015;Furuya et al, 2013;Grulova et al, 2015;Guzen et al, 2012;Kang et al, 2013;Lee et al, 2008Lee et al, , 2010Meijs et al, 2004;Meng et al, 2008;Shin et al, 2014;Tsai et al, 2006;Wu et al, 2008). A recent study successfully delivered FGF2 (a known mitogen for stem cell self-renewal) via subcutaneous injection to give improved outcomes (Goldshmit et al, 2014).…”
Section: Fibroblastic Growth Factorsmentioning
confidence: 98%
“…1 , 2 ) [see also Kim et al, 2009;Shin et al, 2014;Cox et al, 2015;Papa et al, 2016]. These polymers have been widely used in many applications, give consistent release profiles and show minimal toxic effects in both in vitro bioassays and in vivo injections.…”
Section: Use Of Chabc-releasing Nanoparticles Within a Rodent Model Omentioning
confidence: 99%
“…The normal function of the BSB is to protect the spinal cord from toxins and, because it is so efficient, it also excludes the vast majority of therapeutic agents [Pardridge, 2005]. Nanoparticles are being developed that facilitate passage through the BSB and facilitate extended therapeutic delivery at lesions, cell tracking, and/or imaging in the brain and spinal cord [Hu et al, 2009;Zhao et al, 2009;Wiley et al, 2013;Shin et al, 2014]. The advancement of nanoparticle technologies has the potential to lead to innovative translational therapies in the spinal cord, some of which are highlighted in this review.…”
Section: Introductionmentioning
confidence: 99%